New complementary and alternative therapies to control methicillinresistant staphylococcus aureus (MRSA) infection - Diniz, Susana Nogueira; Passeti, Tânia Aguiar; de Souza Marquez, Audrey; Prado, Everton Tadeu; da Silva, Claudia Forlin; dos Santos Baeta, Danielli [UNESP]; Sivieri, Katia [UNESP] (My University, 2020)
Methicillin-Resistant Staphylococcus aureus (MRSA) became a major public health concern worldwide. The increase in the prevalence of antibiotic resistant pathogens, the limited efficacy and the adverse events associated with antibiotics have urged the development of complementary and alternative methods to treat Staphylococcus aureus (S. aureus) infections. This chapter provides a compact overview of the feasibility and clinical impact of novel therapies, with a focus on monoclonal antibodies (mAbs), vaccines, bacteriophages, liposomes and nanotechnology, photodynamic therapy (PDT), homeopathy and botanical medicine. Clinical trials with mAbs carried out in subjects with staphylococcal infections demonstrated that the majority failed to prove the efficacy and only a few remain in clinical development. Vaccines targeting S. aureus have recently been tested in clinical trials and although the results seem promising, there is currently no vaccine which has proven to be clinically effective. Several case studies have demonstrated the use of bacteriophages to treat infections caused by S. aureus. Although this kind of treatment demonstrated to be safe and effective, trials involving a larger population are necessary prior to confidently implement bacteriophages into clinical use. The potential use of liposomal compounds for the treatment of staphylococcal infections and to encapsulate antimicrobial agents as delivery methods, has recently emerged. Results showed that the application of liposomes improves the stability of antimicrobial agents and extends the length of activity, being a promising formulation for bacteria targeted delivery and immune system defense. Antibacterial PDT is a new non-antibiotic treatment strategy for a variety of drug-resistant bacteria including MRSA. Findings on recent studies suggest that PDT can effectively inhibit MRSA by damaging cell membrane, cytoplasm, proteins and nucleic acid. The study of plant extracts with antimicrobial activity allows the identification of active molecules and their mechanism of action, which increases the likelihood of new antimicrobial drugs development or their use in association with known antibiotics to enhance antimicrobial activity. Finally, homeopathic treatment may improve the clinical condition of patients, reduce the need for conventional antimicrobial agents and decrease the relapse rate of infection. Promising results have been obtained with the use of Belladona and MRSA isotherapic to inhibit MRSA growth in vitro, suggesting that this phenomenon was not due to bacterial cell death, but rather to a marked decrease in its growth rate, which probably make the bacteria more sensitive to oxacillin. As discussed in this chapter, there are several promising new complementary and alternative therapeutics towards MRSA that may be successfully used in combination with the available conventional antibimicrobial treatments.
Keywords: Bacteriophages; Botanical medicine; Complementary and alternative therapies; Homeopathy; Liposomes; Methicillin-resistant staphylococcus aureus (MRSA); Monoclonal antibodies (MABS); Nanotechnology; Photodynamic therapy (PDT); Vaccines